Oxford Research Encyclopedia of Psychology 2020
DOI: 10.1093/acrefore/9780190236557.013.747
|View full text |Cite
|
Sign up to set email alerts
|

Political Skill at Work and in Careers

Abstract: Organizations are political environments, and, thus, individuals engage in political behavior in the workplace. As research on organizational politics grew, it became clear that some individuals are more successful at managing this landscape than others. This construct, termed political skill, was designed to capture the social savvy and competencies an individual needs to effectively achieve organizational and/or personal goals. Political skill comprises four key facets: first, social astuteness refers to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…Drawing on socioanalytic theory (Hogan & Shelton, 1998), we identified political skill (i.e., social skill at work) as such a moderator. Not only do these findings support the moderated-expression model for the boldness dimension (Benning et al, 2018), but our study also underscored the high relevance of the political skill construct for work related behaviors in line with previous studies (Kranefeld et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Drawing on socioanalytic theory (Hogan & Shelton, 1998), we identified political skill (i.e., social skill at work) as such a moderator. Not only do these findings support the moderated-expression model for the boldness dimension (Benning et al, 2018), but our study also underscored the high relevance of the political skill construct for work related behaviors in line with previous studies (Kranefeld et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Besides the interpersonal influence domain, political skill also entails social astuteness, networking ability, and apparent sincerity (Kranefeld et al, 2020). Many studies have shown that political skill as a whole improves job performance (e.g., Munyon et al, 2015).…”
Section: Successful Psychopathy and Job Performancementioning
confidence: 99%
“…There is widespread evidence establishing a particular kind of social skill (i.e., political skill) as a critical workplace social competency (Munyon et al, 2015). Due to their acute understanding of others and social interactions, their ability to appear sincere and trustworthy, and their unmatched behavioral versatility, politically skilled individuals appropriately frame and package their behaviors to be well-received by others (Kranefeld et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Auch die Forschung zur politischen Fähigkeit und Geschicklichkeit wartet, wie bereits erwähnt, mit zahlreichen empirischen Studien auf. Einstimmig gehen die Forschenden in diesem Bereich davon aus, dass die politische Fähigkeit eine wichtige Voraussetzung oder ein Prädiktor des beruflichen und führungsbezogenen Erfolgs ist (Kranefeld et al, 2020). In zahlreichen Studien wird der Zusammenhang zwischen der politischen Fähigkeit und der Leistung untersucht, wiewohl hier von einer generellen Betrachtung verabschiedet und eine zunehmende Beachtung des konkreten Arbeitskontextes erfolgt.…”
Section: Beispiele Für Items Zu Dimensionen Der Politischen Fertigkeiten Nachunclassified